Perbandingan kemampuan komunikasi matematis antara model pembelajaran kooperatif tipe teams games tournament (TGT) dan think talk write (TTW) pada materi kekongruenan dan kesebangunan segitiga bagi siswa kelas IX SMP Negeri 2 Binjai T.A 2017/2018 (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
This study aims to see that students' mathematical communication ability using cooperative learning model of Teams Games Tournament (TGT) type is better than Think Talk Write (TTW) cooperative learning model on material of triangle congruence and similarity in class IX SMP Negeri 7 Binjai A.Y. 2017 / 2018. This type of research is a quasi experiment The population in this study is all students of class IX Semester I SMP N 7 Binjai consisting of 8 classes. Sampling was done by cluster random sampling by taking 2 classes from 8 classes randomly that is experiment class A that is class IX-1 which amounted to 32 people and experiment class B that is class IX-8 which amounted to 32 people. This study uses one type of instrument that is post-test only used to determine the ability of mathematical communication that has been validated in the form of a description. From the results of the research given different treatment, experiment class A with cooperative learning model type TGT and experimental class B with cooperative learning model type TTW obtained the average value of experimental class A of 78.683 and the average value of experimental class B of 71.875.Results right t-test with dk = 62 and  = 0.05, obtained t count = 2.09 and t-table = 1.667 so > that is 2.09> 1.667 then Ha accepted, thus obtained the conclusion that the ability of mathematical communication using learning model cooperative type TGT is higher than cooperative learning model type TTW on triangle congruences and similarity subject in IX Grade SMP Negeri 7 Binjai A.Y. 2017/2018.
Keywords: cooperative learning model type teams games tournament (TGT); think talk write (TTW); mathematical communication